Profiling the Preservice Biology Teachers’ Teaching Orientations: Challenges of 21st Century Learning - Listiani Listiani; Aidil Adhani (Scientiae Educatia: Jurnal Pendidikan Sains, 2023)
Teacher's teaching orientations represent teachers' preference in selecting teaching methods that are part of their thinking process and decision-making. Because of the variety of classroom situations, the condition of the students, and the topics to be taught, different teachers might have different preferences for teaching their classrooms. As novice teachers still learn and acquire information regarding the actual classroom setting, this research aims to determine their preference for teaching instructions. Forty-six preservice biology teachers participated in this study. The data was collected using the online version of Indo-POSTT (Pedagogy of Science Teaching Test) was used to understand the preservice teachers' teaching orientations. This formative instrument has been implemented to assess pre- and in-service science teachers' teaching orientations but has never been done widely in Indonesia. Statistically, the study results show that our respondents preferred the more teacher-centered approaches instead of student-centered ones. Active Direct instruction is the most preferred teaching method, while inquiry instruction is the least preferred. This information is especially essential for teacher training institutions to prepare preservice teachers best qualified by understanding the teaching approaches they selected for teaching in the classroom.